Effective Production of Sorbitol and Mannitol from Sugars Catalyzed by Ni Nanoparticles Supported on Aluminium Hydroxide - Rodiansono Rodiansono; Shogo Shimazu (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2013)
Effective production of hexitols (sorbitol and mannitol) was achieved from sugars by means of nickel nanoparticles supported on aluminium hydroxide (NiNPs/AlOH) catalyst. NiNPs/AlOH catalyst was prepared by a simple and benign environmentally procedure using less amount of sodium hydroxide. ICP-AES and XRD analyses confirmed that the NiNPs/AlOH catalysts comprised a large amount of remained aluminium hydroxide (i.e. bayerite and gibbsite). The presence of aluminium hydroxide caused a high dispersion Ni metal species. The average Ni crystallite sizes that derived from the Scherrer`s equation for former R-Ni and NiNPs/AlOH were 8.6 nm and 4.1 nm, respectively. The catalyst exhibited high activity and selectivity both hydrogenolysis of disaccharides (sucrose and cellobiose) and monosaccharides (glucose, fructose, and xylose) at 403 K for 24 h. The NiNPs/AlOH catalyst was found to be reusable for at least five consecutive runs without any significant loss of activity and selectivity. © 2013 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)